Islamic, Pancasila, and Constitutional Approaches to Green Financial Crime in Indonesia - Thani, Shira; Syahrin, Alvi; Thaib, Hasballah; Ekaputra, M. (International Journal of Law and Society, 2025)
Green This research explores the normative, ethical, and constitutional foundations necessary for addressing green financial crime in Indonesia through an integrated framework that combines Islamic jurisprudence, Pancasila values, and constitutional environmental mandates. While financial misconduct causing ecological harm, such as the misuse of climate funds or carbon trading fraud, continues to escalate, Indonesia's environmental legal framework lacks clear definitions and effective enforcement mechanisms to address such crimes adequately. This study employs a normative legal research method, incorporating statutory, conceptual, comparative, and futuristic approaches, supported by content analysis to examine existing regulations' limitations and alternative normative systems' potential contributions. Islamic legal principles such as ʿadl, maṣlaḥah, mīzān, and sadd al-dharīʿah offer a moral foundation for establishing ecologically responsible financial governance. At the same time, Pancasila affirms a justice-based model rooted in national ideology. Furthermore, constitutional guarantees of the right to a healthy environment remain under-enforced due to legal fragmentation and institutional barriers. This research advocates for a value-based reform model that frames environmental protection as an administrative task and a multidimensional ethical obligation grounded in religious, philosophical, and constitutional perspectives. It proposes a framework for more accountable, sustainable, and spiritually rooted environmental governance in Indonesia.